Perspectives for the development of an archeology of the African diaspora in Peru: Preliminary results of the Haciendas de Nasca archaeological project - . Weaver, Brendan J. M (2012)
During Peru’s colonial period, free and enslaved peoples of African descent not only made up a significant portion of the coastal population, but could be found living and working throughout the entire Andean region. Yet these populations have been underrepresented in archaeology or rendered invisible by methodologies and questions which have not directly engaged this diaspora. This article advocates for the development of an interdisciplinary examination of the history and material culture of the African diaspora to Peru which emphasizes the potential for the contributions of archaeology. It also presents the preliminary findings from the 2012/2013 field season of the Haciendas of Nasca Archaeological Project, the first project in Peru to feature a principal research agenda on the material culture of African descent. Through a comprehensive archaeological and historical examination of the Jesuit haciendas of Nasca (1619-1767), PAHN sheds light on both the coercive structures of hacienda labor and some of the ways enslaved Africans expressed their own agency.